Birth of Robin Elliott Watkins At Fresno Community Hospital - Watkins, Howard::::::::: (1982)
Howard Watkins, Adam Watkins, Christine Watkins sitting up in hospital bed, Jerry Kamp, Frances Kamp in Room 330